The effects of computers and acquired skills on earnings, employment and college enrollment: Evidence from a field experiment and California UI earnings records. (April 2018) - Fairlie, Robert W.; Bahr, Peter Riley
Highlights: We experimentally estimate the effects of computers and skills on earnings, employment and college enrollment. Administrative data on earnings, employment and college enrollment are matched to all study participants for seven years. The experiment does not provide evidence that computer skills have short- or medium-run effects on earnings or employment. We do not find evidence of positive or negative effects on college enrollment. Abstract: This paper provides the first evidence on the earnings, employment and college enrollment effects of computers and acquired skills from a randomized controlled trial providing computers to entering college students. We matched confidential administrative data from California Employment Development Department (EDD)/Unemployment Insurance (UI) system earnings records, the California Community College system, and the National Student Clearinghouse to all study participants for seven years after the random provision of computers. The experiment does not provide evidence that computer skills have short- or medium-run effects on earnings. These null effects are found along both the extensive and intensive margins of earnings (although the estimates are not precise). We also do not find evidence of positive or negative effects on college enrollment. A non-experimental analysis of CPS data reveals large, positive and statistically significant relationships between home computers, and earnings, employment and college enrollment, raising concerns about selection bias in non-experimental studies.